Effect of different solvents extraction on recovery of pigments in Xylocarpus granatum, endangered medicinal plant - Hasni, Z.; Yaacob, J.S.; Yusoff, A.I.M.; Taha, R.M.; Ali Ahmed, A.B.; Yahya, R.; Ramesh, K. (2011)
Xylocarpus granatum is locally known as Pokok Nyireh Bunga. This endangered mangrove species has economical importance. Pigments of X. granatum were investigated in the mature leaves of seedlings collected from Carey Island, Selangor, Malaysia. The pigments were solvent extracted using 80 methanol, 80 acetone, 80 N,N-dimethylformamide and 100 hexane. As recommended by Bertrand and Schoefs, all the extraction steps were performed under weak light intensity to avoid photosynthetic pigment degradation. The pigments were detected by ultraviolet-visible spectroscopy and thin layer chromatography. Aqueous acetone was the best solvent for pigment extraction compared to methanol, N,N-dimethylformamide and hexane.